Новые виды рода Pratilepus (Lagomorpha, Leporidae) из плиоценовых отложений кучурганской толщи - Топачевский, И.В. (Вестник зоологии, 1980)
The paper presents illustrated description of two species new for science: Pratilepus kutschurganicus and P. ucrainicus. The former is with an open inner fold on P3 and the latter with the closed inner fold. Both species are from the Pliocene deposits of the Kuchurgan river (Odessa Region, Ukr. SSR) and possess morphological characters similar to those in American representatives of this genus.